Prevalence of prior HIV testing and associated factors among MSM in Zhejiang Province, China: a cross-sectional study - Runhua Li; Xiaohong Pan; Qiaoqin Ma; Hui Wang; Lin He; Tingting Jiang; Dayong Wang; Yan Zhang; Xingliang Zhang; Shichang Xia (BMC, 2016)
Abstract Background Men who have sex with men (MSM) have become one of high-risk population for human immunodeficiency virus (HIV) infection, due to their multiple sex partners and unprotected anal intercourse. Promoting HIV testing is an effective strategy for the prevention and control of HIV infection. We assessed the factors associated with a prior HIV testing history, which could provide guidance for implementation of future HIV intervention programs. Methods A cross-sectional study was conducted in three cities of Zhejiang Province, namely, Hangzhou, Ningbo and Wenzhou, using respondent-driven sampling, between December 2013 and June 2014. A face-to-face questionnaire survey was employed to collect relevant information about HIV testing. Univariate and multivariate logistic regression analyses were used to identify the factors associated with a prior HIV testing history. Results The adjusted rate of prior HIV testing among MSM in Zhejiang Province was 55.9 %. The adjusted rates of HIV and syphilis infections among MSM in Zhejiang Province were 14.0 % and 11.4 %, respectively. A weighted multivariate analysis showed that MSM of older age were more likely to be tested, as were MSM with higher level of education, self-reported homosexuality and a higher frequency of receiving AIDS/sexually transmitted infections educational intervention in the past year. MSM with suicidal inclination and self-perceived lower possibility of HIV infection were less likely to report ever having undergone an HIV test. Conclusions The prevalence of prior HIV testing among MSM in Zhejiang Province, China is low. Effective and more frequent interventional measures should be adopted to improve risk awareness and psychosocial support for younger, less educated MSM, and to encourage more MSM to undergo HIV testing.